Pengetahuan dan Sikap Siswa di Pantai Timur Kabupaten Serdang Bedagai Terhadap Ekosistem Mangrove - Ginting, Elisa Hestita; Syarifuddin, Syarifuddin; Manurung, Binari (Magister Pendidikan Biologi, Universitas Negeri Medan, 2017)
This study aims to determine the level of knowledge about mangrove ecosystems and attitudes towards the preservation of mangrove ecosystems in school students in Serdang Bedagai District. The level of knowledge of students is obtained through the tests of knowledge and questionnaires about the students attitudes toward the preservation of mangrove ecosystems. The results showed that the level of knowledge of high school students in Serdang Bedagai Regency about mangrove ecosystem in general, including enough category with the highest level of knowledge is quite good (60.5%). However, their attitude towards conservation of mangrove ecosystem is categorized as very good (53.8%) and good (42.0%). This indicates that it is necessary to integrate material about mangrove ecosystem in Biology lesson for students who attended school on the East coast of Sumatra.